PHÂN TÍCH HIỆU QUẢ KỸ THUẬT CỦA MÔ HÌNH ĐỘC CANH BA VỤ LÚA VÀ LUÂN CANH HAI LÚA MỘT MÀU TẠI CHỢ MỚI - AN GIANG NĂM 2004-2005 - Nhựt, Quan Minh (Tạp chí Khoa học Đại học Cần Thơ, 2006)
ABSTRACT This paper devotes to find out and to measure the household technical efficiency by the two selected farming patterns in Cho Moi District, AnGiangProvince. Along with this, the author tries to make some conclusions from findings more valuable by computation of economies in scale from which we can infer whether scale efficiency existed or not. Moreover, the conclusions are also corroborated through the sampling method for data and hypothesis testing such as randomly sampling method and One-sided generalized likelihood ratio test (LR), respectively. For the cross-sectional data obtained for the 2004/05 agricultural year, Cobb-Douglas stochastic frontier input distance functions (SFIDF) are found to be adequate representations of data. The empirical results indicate that farmers with continuous rice pattern are more technically efficient than farmers with crop rotation pattern. Keywords: Efficiency, technical efficiency, scale efficiency, continuous rice pattern, crop rotation pattern, stochastic frontier input distance function Title: A technical efficiency analysis of the monoculture with three rice crops and crop rotation pattern with two rice crops and one cash crop in Cho Moi district, An Giang province in the year 2004-2005